1983
DOI: 10.1002/ijc.2910310317
|View full text |Cite
|
Sign up to set email alerts
|

Collagenase activity in rabbit carcinoma: Cell source and cell interactions

Abstract: Fibroblast-like cells (F-cells) and epithelial-like (E-cells) derived from cultures of rabbit VX-2 carcinoma released collagenase in both active and latent forms in serum-free medium at a level higher than that of normal rabbit fibroblast cultures. The enhanced capacity of the F-cells to release the enzyme, however, continued only for a few passages and then decreased significantly to a low level similar to that of the normal fibroblasts. The enzyme-release by the E-cells continued for a few more passages at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…Many studies have examined the role of collagenolytic enzymes in tumour invasion and metastatic spread (for reviews see Woolley et al, 1980;Liotta et al, 1982; and recently several investigations have emphasised the importance of tumour:host cell interactions in connective tissue degradation (Tarin, 1976;Dabbous et al, 1977Dabbous et al, ,1983aBiswas, 1982;Henry et al, 1983). The tumour: host interface or 'invasion zone' (Strauli, 1980) of many invasive tumours is variable with regard to the type and relative numbers of host cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have examined the role of collagenolytic enzymes in tumour invasion and metastatic spread (for reviews see Woolley et al, 1980;Liotta et al, 1982; and recently several investigations have emphasised the importance of tumour:host cell interactions in connective tissue degradation (Tarin, 1976;Dabbous et al, 1977Dabbous et al, ,1983aBiswas, 1982;Henry et al, 1983). The tumour: host interface or 'invasion zone' (Strauli, 1980) of many invasive tumours is variable with regard to the type and relative numbers of host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Collagenase was assayed by measuring the release of soluble radioactive peptides from 30 pl 14C-glycine-labelled reconstituted gel of collagen fibrils (Dabbous et al, 1983a) after 16h at 350C. One unit of collagenase degrades 1 jg collagen min 1 at 35°C and data is expressed as cumulative units per mg protein per 3 days of culture (Dabbous et al, 1983b).…”
Section: Histologymentioning
confidence: 99%
“…Rabbit VX2 carcinoma cells donated by Hanoch Alpern-Elran of this institute were a line grown in DMEM with 10% FBS from primary cultures of an enzyme-digested VX2 tumor. 51 These cells were seeded 1 week before experiments. All cell cultures were maintained at 37°C in an atmosphere of 95% air/5% CO 2 with a relative humidity of 95%.…”
Section: Cell Culturementioning
confidence: 99%
“…In fact, two subpopulations, each lacking a necessary but different enzyme, might be complementary so that a mixture of the two 'nonmetastatic' cells would metastasize. In some cases, the enzyme production itself may be the result of cellular interactions [91][92][93][94][95][96][97][98]. Lygns et al [91] found that two variants of a rat mammary carcinoma were interdependent.…”
Section: Invasion and Intravasationmentioning
confidence: 99%